The Ashgate research companion to military ethics - Johnson, James Turner; Patterson, Eric 1971- (Justice, international law and global security, 2015)
Provides scholars and graduates, serving and retired military professionals, members of the diplomatic and policy communities concerned with security affairs and legal professionals who deal with military law and with international law on armed conflicts, with a comprehensive review of the research in the area of military ethics.